Digital economy - trans-epoch development - Zhang, Zhengyi (БНТУ, 2021)
In recent years, with the rapid development, accelerated maturity and commercial transformation of emerging digital technologies represented by cloud computing, big data, Internet of Things, mobile Internet, artificial intelligence, etc., the digital economy has become the most innovative and fastest growing in economic development. The most influential industry sector.